2002
DOI: 10.1007/s00330-002-1342-1
|View full text |Cite
|
Sign up to set email alerts
|

New frontiers in CT imaging of airway disease

Abstract: Combining helical volumetric CT acquisition and thin-slice thickness during breath hold provides an accurate assessment of both focal and diffuse airway diseases. With multiple detector rows, compared with single-slice helical CT, multislice CT can cover a greater volume, during a simple breath hold, and with better longitudinal and in-plane spatial resolution and improved temporal resolution. The result in data set allows the generation of superior multiplanar and 3D images of the airways, including those obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(79 citation statements)
references
References 102 publications
0
72
0
7
Order By: Relevance
“…These scoring systems have been applied in several diseases [35][36][37][38][39][40][41][42][43][44][45]. Scoring systems rely on the subjective detection and grading of direct and indirect signs of airway disease, such as airway wall thickening, bronchiectasis, mosaic perfusion and/or gas trapping [46][47][48][49][50]. However, qualitative studies are sensitive to the display settings (window width and level) of the images, are prone to inter-and intra-reader variability, and are time consuming and, therefore, expensive.…”
Section: Computed Tomographic Imaging Of the Airways Pa De Jong Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…These scoring systems have been applied in several diseases [35][36][37][38][39][40][41][42][43][44][45]. Scoring systems rely on the subjective detection and grading of direct and indirect signs of airway disease, such as airway wall thickening, bronchiectasis, mosaic perfusion and/or gas trapping [46][47][48][49][50]. However, qualitative studies are sensitive to the display settings (window width and level) of the images, are prone to inter-and intra-reader variability, and are time consuming and, therefore, expensive.…”
Section: Computed Tomographic Imaging Of the Airways Pa De Jong Et Almentioning
confidence: 99%
“…Although such ''gas trapping'' is apparent even in asymptomatic individuals who have normal lung function [86], it is markedly increased in patients with asthma and the degree of gas trapping is related to abnormalities of lung function [33,34,48,70,87].…”
Section: Gas Trappingmentioning
confidence: 99%
“…A recent paper suggests a novel approach, using the intermediate density voxels (2900 to 2950 HU) as a measure of air trapping on expiratory scans compared with inspiratory scans, without the diluting effect of the lowattenuation voxels below 2950 HU that are presumed to show fixed emphysema (40). Reviews of the literature on CT in emphysema have recently been reported and may be useful as additional background information (25,(45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…The tracheal index can be calculated as a ratio of the coronal diameter (mm) by the sagittal diameter (mm). The normal value is approximately one [6] . The angle of the tracheal bifurcation, also called the carinal angle, can vary widely even in normal individuals.…”
Section: Structural Anatomymentioning
confidence: 96%
“…It can result from a wide variety of causes. MDCT with 3-D reformations from the isotropic data acquisitions allows excellent imaging of the entire tracheabronchial tree in one breath hold and is capable of demonstrating clinically significant outflow obstruction using inspiration and expiration imaging in combination, as well as the full extent of the disease process with additional applications like cine-CT and virtual bronchoscopy [6,[32][33][34] .…”
Section: Tracheal and Bronchial Narrowingmentioning
confidence: 99%